CRYPTOCURRENCY DALAM PANDANGAN FATWA MUI, UNDANG-UNDANG, PERATURAN BAPPEBTI, DAN PERATURAN BANK INDONESIA - Titiek Ulfiaty Ismail. L (Jurnal Ekonomi dan Bisnis, 2024)
This study contains two problem formulations, namely: (1) How is cryptocurrency in view of the Law, BAPPEBTI Regulations, and Bank Indonesia Regulations? (2) How is cryptocurrency in view of the MUI Fatwa? This research is qualitative research in the form of document studies. This research is a type of qualitative research in the form of a document study. The primary data sources for this research are laws, BAPPEBTI regulations, Bank Indonesia regulations, as well as sharia references, namely the related MUI fatwas. The secondary data sources for this research are theories, concepts, data and other research related to formal legal regulation of cryptocurrencies. This research resulted in the conclusion that (1) Cryptocurrency according to the law, BAPPEBTI and PBI may not be used as a medium of exchange/currency because (a) Rupiah is the only valid and legal currency in the Republic of Indonesia; (b) Payment system service providers are not permitted to process transactions using virtual currency. Cryptocurrencies as commodities (crypto assets) are permitted to be traded on futures exchanges. However, if crypto assets are used as sharia derivative contracts that are traded on futures exchanges, they must obtain a fatwa from the National Sharia Council of the Indonesian Ulama Council. (2) Cryptocurrency in the MUI Fatwa, is not permitted as a medium of exchange/currency as long as permission is not obtained from authoritative parties, for example UU, BAPPEBTI, and PBI. As for cryptocurrency as a sil'ah (commodity asset), it is permissible if: (a) has a beneficial value; (b) there is an underlying asset, this is to avoid gharar and dharar. As for cryptocurrencies that have no useful value/do not have underlying assets, then they are not allowed to become sil'ah (commodity assets), this is because there is gharar (uncertainty, unclear, high speculation) and dharar (potential danger), if without collateral assets (underlying assets).